Reflection of Political and Social Influences on the Ghazal Genre in Azerbaijani Literature in the 20th Century: Aliagha Vahid's Literary Works (ENTHYMEMA, 2024)
The essay focuses on the problems that hindered the ghazal genre from developing and how the poet kept the tradition alive in Azerbaijani literature at the start of the 20th century. We used Aliagha Vahid’s literary creativity for our project since he lived through this period in Azerbaijan, experienced all of its hardships, and demonstrated the genre’s potential by creating poetic imagery of the time in his ghazals. He is an Azerbaijani poet who is revered in the Turkic community as Fuzuli’s successor and is credited with saving the ghazal genre in Azerbaijani literature. Analyzing his lyrics provided excellent possibilities to examine the influential factors on all of the Azerbaijani literature at the time. In the study, his creation of new kinds of ghazals with social and political issues while retaining the characteristics of the traditional ghazal genre was investigated. With him, the genre in Azerbaijani literature underwent a new phase. The attempt to eradicate the ghazal from the Azerbaijani literature which has a history of centuries –long history did not succeed as a result of mostly Aliagha Vahid’s serious efforts. For this purpose, the poet’s historical milieu, the challenges of the repression, his satirical ghazals with a sociopolitical theme, the thematic details of his lyrics, and other issues have been involved in the investigation.
Keywords: Azerbaijani Literature; Aliagha Vahid; Satirical Ghazal; Socio-political Themes